SURVEY GEOFISIKA METODE RESISTIVITAS 2-D UNTUK MITIGASI BENCANA LONGSOR DI LINTASAN KERETA API PURWAKARTA - PADALARANG - -, Nana Sulaksana; -, Inu Zaini Yasir (Bulletin of Scientific Contribution, 2013)
Landslide problems can result in loss of life or property, environmental damage, destruction of infrastructure and public facilities, as well as disrupt the livelihood of the community. Purwakarta area is indicated as one of the distribution area of Subang claystone formation. This area will potentially somelandslides disasters. Track of rail traffic in this region requires the evaluation of the stability of soil for mitigation purposes. The results showed that the locations of landslide-prone areas lie in the intermediate group resistivity (sand or silty sand or its weathered) which rest on a group of high resistivity of compact claystone.